Assessing the impact of a negative air ionization system on particulate matter and gaseous pollutants in the swine farrowing environment. - Magnus R Campler; Yi-Fan Shen; Leonardo M Klüppel; Andréia G Arruda (PLoS ONE)
Air quality on swine farms has long been a concern for both human and swine health as it has been previously linked with respiratory issues; the main cause being the inhalation of small airborne particulate matter (PM) < 10 μm in diameter. Negative ionizing systems have previously been successfully used to improve air quality in human residential- and commercial buildings as well in agricultural settings. However, less is known about the efficacy of negative ionizing systems in commercial swine farrowing environments. Thus, the objective of this study was to use a swine farrowing environment to evaluate the effects of a negative air ionization system on 1) the quantity of airborne gaseous and particulate matter, and 2) swine health and production parameters. Six farrowing rooms containing 60 sows each were installed with 30 negative ionization systems per room. Three out of six rooms were randomly allocated between active ionization (L-ON) or inactive ionization (L-OFF) between farrowing rounds (N =  4). For each round, measurements of PM2.5, PM10, Ammonia (NH3), hydrogen sulfide gas (H2S), temperature, and humidity were collected twice a week, in the morning and afternoon at two heights, pig level (61 cm) and human level (152 cm). Pig performance metrics (parity, number of piglets born, number of live piglets born, piglet mortality, fostered piglets, and number of weaned pigs) were collected at the end of each batch. Comparisons between L-ON and L-OFF treatments were conducted by averaging room and day specific measurements for all days when rotating rooms shared contrasting treatments. Each room-specific L-ON treatment was then compared to all other L-OFF rooms using a linear regression model. No statistically significant differences were found between treatments for PM2.5 or PM10 at the pig nor human level. However, numerical reductions in the cumulative increase of PM2.5, and PM10 for L-ON rooms compared to L-OFF rooms were found in 60% of the L-ON rooms. One out of five L-ON rooms showed statistically slower buildup of NH3 concentrations compared to L-OFF rooms (P <  0.01) and 60% of the L-ON rooms had significantly slower buildup of H2S concentrations compared to L-OFF rooms (P < 0.01). No effect on production metrics were found between treatments. In conclusion, indications of improved air quality were found in this study, but given the complexity of these types of assessments, further work is needed to conclude the efficacy of negative ionization systems in commercial farrowing systems.